Struktura włókien drewna brzozy brodawkowatej (Betula pendula Roth.) w północno-wschodniej Polsce - Lachowicz, Hubert (Leśne Prace Badawcze, 2010)
Forests of north-eastern Poland are the main raw base of birch. Wood samples were collected from 45 and 70-year-old trees, growing on fresh broadleaved forest site. Statistical analysis was performed for parameters as follows: length, diameter, dimension, thickness of the cell wall, felting index and Runkel rigidity index. Significant influence of location and age of trees on all wood fibers parameters except influence of age on fibers diameter were stated. The highest felting index of wood fibers had birch wood coming from the Płońsk Forest District – 73,27 (the longest fibers and the smallest fibers diameter). The highest Runkel rigidity index of wood fibers was noted in the Giżycko Forest District (the thickest fiber walls) – 5,18.